USING THINK-TALK-WRITE (TTW) STRATEGY TO TEACH VOCABULARY IN DESCRIPTIVE TEXT - Suryani, Florentina; Regina, Regina; Bunau, Eusabinus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe aim of this research was to investigate whether or not Think-Talk-Write (TTW) strategy effective to teach vocabulary in descriptive text and the effect size of Think-Talk-Write (TTW) strategy. The method was a pre-experimental research with one group pre-test and post-test design. The population of this research was the eighth grade students of SMP N 19 Pontianak. The sample of this research was VIII B which consisted of 35 students. The data of this research were collected using measurement technique and the tool of data collecting was multiple choice test. The research findings showed that the mean score of pre-test was 59.7 and the mean score of post-test was 70. Furthermore, the data analyzed using t-test resulted that t-test score (5.271) was higher than t-table (2.032) at 0.05 degree of freedom. It means that theÂ  null hypothesis (Ho) was rejected and the alternative hypothesis (Ha) was accepted. The calculation of effect size of the treatment is 0.89. It is categorized as moderately effective. It can be concluded that the use of Think-Talk-Talk (TTW) strategy is moderately effective to teach vocabulary in descriptive text. So, it is recommended to the teacher to use Think-Talk-Write (TTW) strategy as one of strategies to teach vocabulary in descriptive text.Â Keywords: Think-Talk-Write (TTW) Strategy, Vocabulary, Descriptive Text.